FORMATION OF LEADERSHIP QUALITIES IN ATHLETES THROUGH JUDO TRAINING (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the process of forming leadership qualities in athletes through systematic judo training. Leadership in sports is not limited to the ability to manage a team but also includes self-regulation, decision-making under pressure, communication, and moral responsibility. Judo, as a martial art and educational system, provides a unique foundation for developing these traits through its philosophy of mutual benefit and respect. The study analyzes the pedagogical, psychological, and social mechanisms by which judo fosters leadership potential. It emphasizes the role of the coach as a mentor and the importance of training situations that simulate real-life challenges requiring initiative and emotional balance. The paper concludes that regular participation in well-structured judo programs contributes not only to physical improvement but also to the formation of socially significant leadership skills that extend beyond the sports environment.